Médecine Du Désir : De La Crise De La Reconnaissance De Soi À L’émergence D’une Identité Remodelée - Ekpo, Victorien Kouadio (European Scientific Journal, ESJ, 2016)
The identity of a person is subject to various influences, sources of its modulation, to the point that talking about natural identity becomes controversial. The dynamic of identity experiences a turning point with the medicine of desire. This medicine creates totally new relationships that influence traditional institutions of identity recognition. Abandoning the unilateral and anti-dialectical discourses of essentialists relative to identity, this paper provides with a key insight in the ethical strategies that connects the medicine of desire to the crisis of self-recognition. It consists in clearly underlining with an ethical touch, the biomedical challenges of the dynamic of recognition and identity.